“La capacitación administrativa y el rendimiento laboral en la cooperativa de ahorro y crédito futuro Lamanense del cantón La Maná”. - Yanchaliquin Quishpe, Patricio Misael (2023)
Innovation and knowledge updating represent a factor transcendental in defining a leadership style in the collaborators and designing strategic objectives that improve labor performance. The research analyzes the relationship between training and work performance in the Saving and Credit Cooperative Futuro Lamanense La Maná canton. The type of research is exploratory and descriptive. The population consisted of 21 people, including administrative and management personnel applied an interview and a questionnaire with standardized and structured questions. As a result, 80% of the collaborators consider it necessary to implement a constant training plan, a better work environment, and better performance in administrative skills to achieve their objectives. In addition, a correlation analysis was carried out between training hours and work performance, for instance, the number of employees’ hours who received the training and the number of errors committed in the last months. A negative correlation coefficient of -0.45 showed a negative relationship and that the higher the number of training hours, the lower the number of errors. Therefore, the need to propose a training plan for the Cooperative's collaborators is evident. A training proposal is suggested for the institution's collaborators related to customer service and attention to financial services to improve work performance and hopefully decrease the number of errors made in the activities.